Quality of care for childhood asthma: estimating impact and implications - Mattke, Soeren; Martorell, Francisco; Sharma, Priya; Malveaux, Floyd; Lurie, Nicole (Pediatrics (Evanston), 2009)
We conducted a review of 164 relevant publications to consolidate the evidence on gaps in the quality of asthma care, the impact of those gaps, and the costs and benefits of closing those gaps. Researchers used a wide variety of definitions for measures of quality asthma care, clinical and utilization end points, and disease severity. Gaps in care were most evident for pharmacologic treatment, particularly the underuse of inhaled corticosteroids, with median usage rates of 40%; however, in studies with large proportions of black subjects, the inhaled corticosteroid usage rate was only 32%, compared with 51% for nonminority populations. Studies on outcomes focused on emergency department visits, hospital admissions, and missed school days. Because only 6 studies included information on the costs of improving asthma care, no consensus estimates of the cost/benefit ratio for better asthma care could be derived. There was insufficient evidence in the literature for assessment of the impact of gaps in care and the costs of closing those gaps. More economic evaluations of the impact of gaps in asthma care and of interventions to improve asthma control are needed. Future research on gaps in asthma care and their impact must use standardized definitions for key variables such as disease severity and care utilization to allow comparisons across studies and building of an evidence base that is convincing for policy makers and purchasers of care.